Domestic violence – when the man is the victim We know that no two people are the same, but...!? (Academic Journal of Internal Affairs, 2022)
Aim: The author of the review sheds light on the theoretical and practical concepts related to the professional and scientific field of domestic violence based on professional and academic values and an examination of the relevant field.Methodology: The problem of domestic violence is a very important issue in Hungary, and in most cases the crime remains latent. The article analyses and examines the role of men who are abused by their partners and proves with the results of the research that men have the same right to protection, help and the enforcement of their rights as women.Findings: Reports of domestic abuse are becoming more and more common in the news. In most cases, the reported violence is directed against children and women, and the perpetrators are men who have seriously injured or sexually assaulted their victims. However, there is a hidden side to domestic violence that almost no one, not even the victims themselves, talks about. In the public consciousness, abuse is mainly associated with physical violence. In many cases, the verbal aggression and the psychological trauma associated with this and physical violence leave a deeper mark on a victim than the physical pain.Value: The study provides a different perspective on the issue of domestic violence. It looks at what it is like when a man is the victim. According to social expectations, men are strong, all-tolerant individuals, crying is not accepted from them as it is a sign of weakness. Men are taught to grow up knowing that it is not appropriate to hurt a woman. This is a principle he holds on to almost at all costs, even when his partner is aggressive towards him. He does not talk about his humiliation and tolerates his wife/partner’s daily abuse, whether verbal or physical. If he were to strike back in self-defence, he would usually cause more serious injury than the wounds he has suffered, and if she then sought help, he would have to prove his innocence to the justice system for committing a violent offence.
Keywords: domestic violence; victim protection; male victim